Passing/out : sexual identity veiled and revealed - Cooley, Dennis R., 1965-; Harrison, Kelby (Ashgate, 2012)
Shedding light on the meaning of 'passing' and 'outing' in relation to identity, Passing/Out constructs a dialogue between the work of scholars whose intellectual careers began prior to the advent of queer theory and those whose work has been more immediately and directly shaped by this approach, with a view to breaking new ground in the field of identity.